(untitled) (Med Phoenix, 2022)
We presented a person with psychological distress symptoms before the onset of COVID-19 (coronavirus disease) outbreak. In January 14, 2020, a 23-year-old female with a negative past medical history presented with complaint of difficulty in breathing and swallowing, feeling breathlessness, tightness, and pain in her chest. She was suffocating and needed to open windows or go out of the room to breathe. She felt that something is stuck in her throat or chest and always hurts herself too much. She felt nervous nearly every day and easily became irritable and restless most of the time and can’t relax. The patient was panicky and restless, dizziness with a dry mouth and cold and sweaty extremities, mild tachypnoea and mild tachycardia on physical examination. The patient was generally oriented and cooperative with no suicidal ideation or thoughts. Mental status of the patient was improved after twice the consultation visit.